Teens and young people with disabilities purchased physical violence: representations about disability - Fabiana Paulino Alves; Inácia Sátiro Xavier de França; Gabriela Maria Cavalcanti Costa; Maria Emília Limeira Lopes; Rosilene Santos Baptista (Universidade Federal do Ceará, 2013)
This study aimed to understand the representations of disability of adolescents and young people with disabilities acquired by violence. It was exploratory, descriptive, qualitative study was conducted in UBSF of Campina Grande, the period October 2011 to February 2012. In the universe of thirteen subjects, nine constituted the sample. Used as instruments form and semi-structured interviews. In the interviews we used the Content Analysis Categorical Theme ruled in the Theory of Social Representations. In the results, enunciated three categories are: representations on disability from anatomic changes; representations of feelings experienced disability and lack of representation of the term disability. The disability acquired in adolescence or youth as a result of violence brings indelible mark, representing biopsychosocial difficulties and limitations, compromising the quality of life.